La publicidad en los canales de televisión tv color y tv micc del cantón Latacunga y su contribución a la cultura y educación de la sociedad cotopaxense en el periodo 2014-2015 - Quimbita Chicaña, Hugo Armando (2016)
The goal researchis investigate on: “Theadvertising attelevisionchannelscolor and MICC tv in Latacunga cantonon their cultureand educationsociety contributioncotopaxense during 2014-2015”.In Chapter I the theoretical foundation of the research work, which includes topics such as semiotics, advertising, advertising psychology, communication, media and television is developed. The methodology is deductive because it allows to know essential foundations from its origins to today….